Interpreting the Prevalence of Mental Disorders in Children: Tribulation and Triangulation - Holbrook, Joseph R. (Health Promot Pract, 2016)
Knowledge on the prevalence of mental disorders among children informs the work of many health care providers, public health researchers, educators, and policy makers, and any single data source and study methodology can provide valuable insight. However, it is only after prevalence estimates from complementary studies are considered together that distinctions can be made to more deeply inform an assessment of community needs, including diagnosed prevalence versus underlying prevalence, differences between insured and uninsured populations, and how estimates change over time. National surveys, community-based studies, and administrative claims data each provide a different type of information that builds broad understanding. This article presents some of the overarching complexities of the issue, discusses strengths and weaknesses of some common data sources and methodologies used to generate epidemiological estimates, and describes ways in which these data sources complement one another and contribute to a better understanding of the prevalence of pediatric mental disorders.